Discurso, fake news e comunidade surda: uma análise discursiva de perigosos consensos - Santos, Wesley Nascimento (Universidade Federal de São Carlos, 2026)
Numerous studies have addressed the phenomenon of fake news, particularly within the field of communication studies and, more broadly, in the humanities. While these studies are often rigorous and well-intentioned, they tend to be grounded in a premise that, in the short term, has proven to be of limited effectiveness. This premise involves combating fake news by focusing either on their “content” or on their formal structure, with the goal of fostering more critical and competent readers. In this sense, scholars seek to understand the social, political, psychological, communicative, or linguistic regularities underlying fake news and, based on that understanding, propose practical actions aimed at digital literacy. However, such approaches often overlook the fact that fake news are discursive productions that circulate within diverse and segmented discursive communities. Given the questionable short-term efficacy of approaches that prioritize content analysis and assume a relatively undifferentiated public, this study aims to conduct a discursive analysis of fake news by examining their historical constitution, linguistic formulation, and social circulation within Deaf communities, particularly through posts, messages, and other digital social media content. Our analytical framework draws on the principles, concepts, and methods of French Discourse Analysis, rooted in the work of Michel Pêcheux and his research group, alongside Michel Foucault’s reflections on the order of discourse. This framework allows us to identify which interdiscursive elements are repeated, reformulated, or silenced in the discourses that propagate distorted versions of factual reality, as well as the linguistic strategies employed, the materialities through which such discourses are disseminated, and the social and institutional spaces they inhabit. Through the description, interpretation, and discursive comprehension of utterances in which fake news are materialized within Deaf communities, the findings of this study aim to inform and support the development of public and social policies for countering these forms of discursive distortion and for promoting discursive and digital literacy.
Discourse, fake news, and the deaf community: a discursive analysis of dangerous consensuses
Keywords: Fake news; Análise do discurso digital; Comunidade surda; Análise do discurso; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA; 10. Redução das Desigualdades